Enhanced tensile properties in a Mg-6Gd-3Y-0.5Zr alloy due to hot isostatic pressing (HIP). Issue 9 (September 2019) - Zhou, B.; Wu, D.; Chen, R.S.; Han, En-hou
Abstract: Hot isostatic pressing (HIP) was applied to Mg-6Gd-3Y-0.5Zr (GW63) alloy to reduce shrinkage porosity, thus, to enhance the integrity and reliability of castings. During HIP process, shrinkage porosity was closed by grain compatible deformation and subsequent diffusion across the bonding interface. The amount of initial shrinkage porosity was the key factor for shrinkage porosity closure. HIP was testified to be effective on shrinkage porosity reduction in GW63 alloy due to its relatively narrow solidification range and resultant low content of initial shrinkage porosity in most sections, leading to higher tensile properties both in as-cast and cast-T6 condition. The improvement in tensile properties was mainly because of shrinkage porosity reduction and resultant effective rare-earth (RE) elements homogenization and precipitation strengthening.